1983
DOI: 10.1159/000206884
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for an Erythropoietin-Stimulating Factor in Patients with Renal and Hepatic Disease

Abstract: Recently, a factor was discovered in the serum of hepatectomized animals which was capable of augmenting the hepatic erythropoietin response to hypoxia when injected into normal rats. This substance was localized in the liver via an in situ perfusion technique and was termed the hepatic erythropoietic factor (HEF). Patients with kidney disease, liver disease, and combined renal and hepatic disease were studied in this report. Detectable HEF levels were found in the plasma of patients with both liver and kidney… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1989
1989
2003
2003

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…Anemia is frequently seen in cirrhotic patients 27–29 and it is also known that the liver can produce as much EPO as the kidney normally produces in the state of anemia 10,18 , 34,35 . Consistent with previous studies, the present study also demonstrated that cirrhotic patients with anemia had higher plasma levels of EPO than those without anemia 18–22 . In contrast, Siciliano et al .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Anemia is frequently seen in cirrhotic patients 27–29 and it is also known that the liver can produce as much EPO as the kidney normally produces in the state of anemia 10,18 , 34,35 . Consistent with previous studies, the present study also demonstrated that cirrhotic patients with anemia had higher plasma levels of EPO than those without anemia 18–22 . In contrast, Siciliano et al .…”
Section: Discussionsupporting
confidence: 90%
“…Siciliano et al 17 . demonstrated a reduced plasma level of EPO in patients with cirrhosis compared with non‐cirrhotic patients, while other studies have shown levels of plasma EPO were higher in cirrhotic patients than in healthy subjects 18–22 . It has been hypothesized that increased blood pressure following EPO therapy in patients with renal failure may possibly result from the trap of nitric oxide (NO) by increased hemoglobin levels with subsequent increased systemic vascular resistance 23 .…”
Section: Introductionmentioning
confidence: 99%